GAMBARAN PENGETAHUAN GIZI DAN SIKAP IBU TENTANG POLA MAKAN BALITA DI DESA BUNGGALO KECAMATAN TALAGA JAYA KABUPATEN GORONTALO - Misnati, Misnati; Satue, Rahmatia (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2018)
ABSTRACT Under-five age is a period of growth and development that is prone to nutrition and requires nutrients in a greater number than other age groups. This study aims to describe the mother's knowledge and attitudes about the diet of under-five children in Bunggalo Village, Talaga Jaya District, Gorontalo.Types this research is descriptive research with a sample of 51 people. Data collection using questionnaire sheets related to under-five children?s diet. Results: 17 mothers (33%) have excellent knowledge, 25 mothers (49.0%) have sufficient knowledge and 9 mothers (17.6%) have insufficient knowlwdge. Meanwhile, mothers? attitude toward children?s diet showed that 23 mothers (45.1%) have favorable attitude, 22 mothers (43.1%) have been classified as sufficient category, and 6 mothers (11.8%) have been classified as insufficient category. The conclusion of this study is that the knowledge of nutrition with the most sufficient categories was 25 people (49.0%) and the attitude of mothers who had been categorized as favorable categories were 23 people (45.1%). Keywords: Mother's knowledge, mother's attitude, under-five children?s diet ABSTRAK Balita merupakan suatu periode pertumbuhan dan perkembangan yang rawan gizi dan memerlukan zat-zat gizi dalam jumlah yang lebih besar dari kelompok umur lain.Penelitian ini bertujuan untuk mengetahui gambaran pengetahuan dan sikap ibu tentang pola makan balita di Desa Bunggalo Kecamatan Talaga Jaya Kabupaten Gorontalo.Jenis penelitian ini adalah penelitian deskritif dengan jumlah sampel 51 orang. Pengumpulan data menggunakan lembar kuesioner Terkait Pola Makan Balita. Hasil penelitian diperoleh pengetahuan ibu terkait pola makan balita yang mempunyai pengetahuan baik 17 orang (33%), cukup 25 orang (49,0%), dan kurang baik 9 orang (17,6%). Sikap ibu balita terkait pola makan balita dalam kategori baik 23 orang (45,1%), cukup 22 orang (43,1%) dan kurang baik 6 orang (11,8%). Kesimpulan penelitian ini adalah pengetahuan gizi yang paling banyak kategori cukup berjumlah 25 orang (49,0%) dan sikap ibu yang banyak kategori baik 23 orang (45,1%).